Developing a Drill-and-Practice-Based Scratching Learning Media to Improve Mathematical Problem-Solving Skills and Students' Mathematics Learning Motivation Junior High School 2, Tebing Tinggi City - Utari, Kania; Rajagukguk, Waminton; Surya, Edy (Universitas Negeri Makassar, 2025)
Students should be able to answer real-life math problems; therefore, mathematical problem-solving is crucial. Math problem-solving is improved by computer media. Educational media that meets students' needs motivates and inspires them, enhancing learning outcomes. Students' quantitative problem-solving skills will improve math learning results. Scratch is a computer-based learning tool that improves learning. The goal of this research is to use Scratch as a learning medium to improve students' mathematical problem-solving skills and motivation to learn mathematics. SMP Negeri 2 Kota Tebing Tinggi 7th graders completed this investigation in 2024/2025. This development research produced a valid, practical, and successful drill-and-practice-based visual learning medium to improve students' problem-solving and learning motivation. Media validity averaged 3.40, material validity 3.60, and linguistic validity 3.79. Teacher questionnaire scores averaged 3.67, while student questionnaire scores averaged 3.13 in the